Dye dispersion system with high-temperature stability and preparation method thereof

By adding xylan to the dispersed dye and mechanically grinding, a dye dispersion system of nano-scale particles is formed, and the problem of poor stability of dispersed dyes at high temperatures is solved, and the high temperature stability and dyeing effect are improved.

CN119708883APending Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810966.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing dispersed dyes have poor stability at high temperatures, resulting in poor dyeing effects, and the existing methods are complex in operation and high in cost.

Method used

A dye dispersion system consisting of dispersed dyes, xylan and water is used to reduce the particle size to the nanoscale through mechanical grinding, enhance electrostatic repulsion, and improve high temperature stability.

Benefits of technology

It significantly improves the high temperature stability and storage and transportation stability of the dye dispersion system, enhances the interaction between the dye and the fiber molecular chain, and improves the dyeing rate, dyeing uniformity, color brightness and color fastness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180532880000091
    Figure BDA0005180532880000091
Patent Text Reader

Abstract

The invention discloses a dye dispersion system with high-temperature stability and a preparation method thereof. The dye dispersion system with high-temperature stability is composed of disperse dye, xylan and water, the weight ratio of the disperse dye to the xylan is 0.25-4, and the mass of the water is 60-90% of that of the dye dispersion system. Excellent amphipathy and heat-resistant stability of xylan and good wrapping property and protectiveness on dye particles ensure that the dye dispersion system with high-temperature stability has the advantages of good normal-temperature and high-temperature stability, wide applicable dye varieties and low reduction destruction rate of azo dyes; and moreover, the biomass is derived from rich and renewable plant biomass, is simple to prepare, is green, degradable and renewable, and is non-toxic and harmless.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dye dispersants, and particularly relates to a dye dispersion system with high temperature stability and a preparation method thereof. Background Art

[0002] Disperse dyes belong to nonionic dyes and are small molecule dyes that do not contain water-soluble groups in a class of structures. Disperse dyes have advantages such as good dyeing fastness and a wide range of adaptability to dye bath pH, ​​so they are widely used. Since disperse dyes usually require high temperature heating during the dyeing process, how to improve the high temperature stability of disperse dyes is a very important issue. In the prior art, the high temperature dispersion stability of disperse dyes is usually improved by changing the structure of disperse dyes, including increasing the molecular weight of the dye, introducing halogen atoms or metal atoms into the molecule, introducing polar groups into the molecule, and making the molecule have a condensed ring structure (Ye Runhui. On improving the high temperature dispersion stability of disperse dyes [J]. Dyestuff Industry, 1994 (4): 10-12.). However, the above method is not only complicated to operate, but also costly. Summary of the invention

[0003] The purpose of the present invention is to provide a dye dispersion system with high temperature stability in view of the problem that the existing disperse dyes have poor high temperature stability.

[0004] Another object of the present invention is to provide a method for preparing the above-mentioned dye dispersion system with high temperature stability.

[0005] To achieve the purpose of the present invention, the technical solution adopted is:

[0006] A dye dispersion system with high temperature stability consists of disperse dye, xylan hemicellulose (hereinafter referred to as xylan) and water, wherein the weight ratio of disperse dye to xylan is 0.25-4, and the mass of water is 60-90% of the dye dispersion system.

[0007] In the above-mentioned high-temperature stable dye dispersion system, the xylan side chains enhance the thermal stability and prevent the dye particles from agglomerating and being hydrolyzed at high temperatures. In addition, the appropriate xylan molecular weight increases the viscosity of the system, reduces the mutual collision caused by high-frequency Brownian motion, and is beneficial to the storage and transportation stability of the dye.

[0008] Preferably, the disperse dye includes (but is not limited to) at least one of azo disperse dyes, anthraquinone disperse dyes, and styrene disperse dyes.

[0009] Preferably, the xylan is extracted from plant biomass raw materials.

[0010] More preferably, the plant biomass raw material includes (but is not limited to): at least one of wood, bamboo, crop straw, xylem of annual herbaceous plants, and fruit shells.

[0011] More preferably, the extraction method includes (but is not limited to): one of an alkali solution extraction method, a dimethyl sulfoxide extraction method, and a low eutectic solvent extraction method.

[0012] Preferably, the weight average molecular weight of the xylan is 20,000 to 100,000.

[0013] A method for preparing a dye dispersion system with high temperature stability comprises the following steps:

[0014] The xylan, water and disperse dye are mixed in a certain mass ratio to obtain a xylan / dye dispersion system, and then the xylan / dye dispersion system is mechanically ground to prepare the dye dispersion system with high temperature stability.

[0015] Preferably, the mechanical grinding method includes (but is not limited to) one of ball milling, sand milling, and high-pressure homogenization. The parameter conditions in the ball milling and sand milling methods are: the type of grinding beads includes (but is not limited to) one of zirconium oxide beads, steel beads, and glass beads, the volume ratio of different grinding beads (0.1-0.5 mm: 1.5-3 mm) is 7:3, the mass ratio of xylan / dye dispersion system to grinding beads is 1:5-1:30, the grinding time is 2-8 hours, and the grinding speed is 100-1000 r / min; in the high-pressure homogenization method, the high-pressure homogenization parameter conditions are: homogenization pressure 50-300 MPa, and the number of homogenization cycles is 5-10 times.

[0016] In the above preparation method, mechanical grinding can efficiently and accurately reduce the particle size of the disperse dye to the nanoscale, greatly increase the specific surface area and surface energy, induce a strong electrostatic repulsion effect, stabilize the stability of the system, and avoid agglomeration.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0018] (1) The dye dispersion system with high temperature stability of the present invention has good high temperature stability and storage and transportation stability.

[0019] (2) In the preparation method of the present invention, the particle size of the xylan-dispersed dye system is reduced to the nanoscale by mechanical grinding, which can simply, greenly and efficiently impart the advantages of small particle size, high specific surface area and surface energy, maintain strong electrostatic repulsion, stabilize the dye system, avoid precipitation due to agglomeration, and further enhance the high-temperature stability of the system, thereby enhancing the interaction between the dye system and the fiber molecular chain, and improving the dyeing rate, dyeing uniformity, color brightness and color fastness.

[0020] (3) The xylan used in the present invention is abundant and renewable, and the preparation process of the dye dispersion system is green, non-toxic and harmless. DETAILED DESCRIPTION

[0021] The present invention is further described in detail below in conjunction with examples and comparative examples, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be directly purchased from the market. For method parameters not particularly noted, conventional techniques can be used.

[0022] Example 1

[0023] The eucalyptus wood is crushed to 40-60 mesh and dried. 100g of the absolutely dry raw material (water content is less than 15%) is weighed and mixed with a sodium hydroxide solution with a concentration of 5.00wt% at a material-liquid ratio of 1:4 (w:v, unit is g / mL) in a rotary high-temperature reactor, and heated from room temperature (25℃) to 155℃ at a heating rate of 2℃ / min and then kept warm for 120min to complete the high-temperature reaction; after the reaction is completed, the reaction liquid is filtered and collected, and the pH is adjusted to 6.0 with hydrochloric acid, and then stirred and added to anhydrous ethanol (the volume ratio of the mixed liquid to ethanol is 1:3) to precipitate xylan, and after standing for 6h, the xylan is separated from the solid and liquid by centrifugation; the separated xylan is continuously washed with an ethanol solution with a volume percentage concentration of 70% for more than three times, and placed in a ventilated place to volatilize the ethanol, and then dried to obtain xylan. The weight average molecular weight of xylan is 71800.

[0024] Xylan and dispersed dark blue S-3BG 2007 dye were dispersed in water to form a xylan / dye dispersion system, wherein the water was 60wt% and the mass ratio of dispersed dye to xylan was 4. Then, the xylan / dye dispersion system was ground using a ball mill to obtain a dye dispersion system with high temperature stability, and the specific parameter conditions were: the mass ratio of the xylan / dye dispersion system to the zirconia beads was 1:5, the volume ratio of the zirconia beads with diameters of 0.1 mm and 1.5 mm was 3:7, the grinding time was 4 hours, and the grinding speed was 400 r / min.

[0025] Example 2

[0026] The bamboo material was crushed to 40-60 mesh, dried and dewaxed, and 100g of the absolutely dry raw material was weighed and mixed with 2500mL of 6wt% NaClO2 solution in a beaker to selectively remove lignin. The specific operation was: continuous stirring and heating for 2h, during which the temperature was maintained at 60°C, the magnetic stirring speed was 400r / min, and acetic acid was used to maintain the solvent environment pH at 4.5. After repeating this operation for more than 2 times, the residue was filtered, washed, and freeze-dried to obtain holocellulose.

[0027] Weigh 100g of the above holocellulose sample and 1500mL of dimethyl sulfoxide reagent in a beaker to mix and extract xylan. The specific operation is: stir and heat continuously for 10h, during which the temperature is maintained at 70℃ and the magnetic stirring speed is 400r / min; after the reaction is completed, filter and collect the reaction solution, stir and add it into anhydrous ethanol (the volume ratio of the mixed solution to ethanol is 1:3) to precipitate xylan, and after standing for 6h, centrifuge to separate the solid and liquid of xylan; wash the separated xylan with 70% ethanol solution by volume for more than three times, and place it in a ventilated place to volatilize the ethanol, and then dry it to obtain xylan. The molecular weight of the obtained xylan is 21200.

[0028] Xylan and disperse red 3B dye are dispersed in water to form a xylan / dye dispersion system, wherein the water is 70wt% and the mass ratio of disperse dye to xylan is 2.75. Then a sand mill is used to grind the xylan / dye dispersion system to obtain a dye dispersion system with high temperature stability. The specific parameter conditions are: the mass ratio of the xylan / dye dispersion system to glass beads is 1:10, the volume ratio of glass beads with diameters of 0.3mm and 2mm is 3:7, the grinding time is 8h, and the grinding speed is 200r / min.

[0029] Example 3

[0030] The oil tea shell is crushed to 40-60 mesh, dried and dewaxed, 100g of the above-mentioned absolute dry raw material is weighed, and a deep eutectic solvent with a concentration of 10.00wt% is stirred and heated at 80℃ for 6h in a closed container at a mass ratio of 1:20. After stirring and heating at 80℃ for 6h, it is diluted with water and separated by solid-liquid separation by centrifugation until the filtrate has a pH of 7.0, and the filtrate is stopped. The recovered filtrate is stirred and added to anhydrous ethanol (the volume ratio of the mixed solution to ethanol is 1:3), and xylan is obtained after standing for 6h. The xylan is separated from the solid and liquid by centrifugation, and the separated xylan is continuously washed with an ethanol solution with a volume percentage concentration of 70% for more than three times, and placed in a ventilated place to volatilize the ethanol, and then dried to obtain xylan. The molecular weight of the obtained xylan is 41900. The deep eutectic solvent is specifically configured as follows: the molar ratio of urea to choline amino acid is 2:1, and after being heated with stirring at 60° C. for 2 hours in a sealed container, water is added to dilute the mixture to 10.00 wt%.

[0031] Xylan and disperse yellow 31 dye are dispersed in water to form a xylan / dye dispersion system, wherein the water is 80wt% and the mass ratio of disperse dye to xylan is 1.5. Then a ball mill is used to grind the xylan / dye dispersion system to obtain a dye dispersion system with high temperature stability. The specific parameters of the ball milling are: the mass ratio of the xylan / dye dispersion system to the steel ball is 1:20, the volume ratio of the steel ball with a diameter of 0.5mm and 3mm is 3:7, the grinding time is 2h, and the grinding speed is 1000r / min.

[0032] Example 4

[0033] The corn stalks were crushed to 40-60 mesh and dried. 100 g of the absolutely dry raw material was weighed and mixed with a sodium hydroxide solution with a concentration of 7 wt% at a material-liquid ratio of 1:4 (w:v, in g / mL) in a rotary high-temperature reactor. The mixture was heated from room temperature (25°C) to 145°C at a heating rate of 2°C / min and kept warm for 180 minutes to complete the high-temperature reaction. After the reaction, the reaction liquid was filtered and collected, and the pH was adjusted to 6 with hydrochloric acid. The mixture was stirred and added to anhydrous ethanol (the volume ratio of the mixed solution to ethanol was 1:3) to precipitate xylan. After standing for 6 hours, the xylan was separated from the solid and liquid by centrifugation. The separated xylan was washed with 70% ethanol solution for more than three times, and placed in a ventilated place to volatilize the ethanol, and then dried to obtain xylan. The molecular weight of xylan is 97600.

[0034] Xylan and disperse orange 30 dye are dispersed in water to form a xylan / dye dispersion system, wherein the water is 90wt% and the mass ratio of disperse dye to xylan is 0.25. Then, a xylan / dye dispersion system with high temperature stability is prepared by high-pressure homogenization, and the specific parameters of high-pressure homogenization are: homogenization pressure of 120MPa, the number of homogenization cycles of 10 times, and the homogenization flow rate of 30L / h.

[0035] Comparative Example 1

[0036] Sodium methylenebisnaphthalenesulfonate (NNO) dispersant and dispersed dark blue S-3BG 2007 dye were dispersed in water and ground using a ball mill to form an NNO / dye dispersion system for use in the xylan / dye dispersion system of Comparative Example 2.

[0037] In the NNO / dye dispersion system constituted by Comparative Example 1, water is 70wt%, and the mass ratio of disperse dye:NNO dispersant is 2.75; the specific ball milling parameter conditions are as follows: the mass ratio of NNO disperse dye system to zirconia beads is 1:5, the volume ratio of zirconia beads with diameters of 0.1mm and 1.5mm is 3:7, the grinding time is 4h, and the grinding speed is 400r / min.

[0038] Comparative Example 2

[0039] Naphthalenesulfonic acid formaldehyde condensate (NMF) dispersant and disperse dark blue S-3BG 2007 dye were dispersed in water and ground using a ball mill to form an NMF / dye dispersion system for use in the xylan / dye dispersion system of Comparative Example 2.

[0040] In the NMF / dye dispersion system constituted by Comparative Example 2, water is 70wt%, and the mass ratio of disperse dye:NMF dispersant is 2.75; the specific ball milling parameter conditions are as follows: the mass ratio of NMF disperse dye system to zirconia beads is 1:5, the volume ratio of zirconia beads with diameters of 0.1mm and 1.5mm is 3:7, the grinding time is 4h, and the grinding speed is 400r / min.

[0041] Comparative Example 3

[0042] The eucalyptus wood is crushed to 40-60 mesh and then dried. 100g of absolutely dry raw material (water content is less than 15%) is weighed and mixed with a sodium hydroxide solution with a concentration of 5.00wt% at a solid-liquid ratio of 1:4 (w:v, unit is g / mL) in a rotary high-temperature reactor, and heated from room temperature (25℃) to 155℃ at a heating rate of 2℃ / min and then kept warm for 120min to complete the high-temperature reaction. After the reaction is completed, the reaction liquid is filtered and collected, and the pH is adjusted to 6.0 with hydrochloric acid, and then stirred and added to anhydrous ethanol (the volume ratio of the mixed liquid to ethanol is 1:3) to precipitate xylan, and after standing for 6h, the xylan is separated from the solid and liquid by centrifugation; the separated xylan is continuously washed with an ethanol solution with a volume percentage concentration of 70% for more than three times, and placed in a ventilated place to volatilize the ethanol, and then dried to obtain xylan.

[0043] Xylan and dispersed dark blue S-3BG 2007 dye were dispersed in water to form a xylan dispersed dye system, wherein the water was 70wt% and the mass ratio of dispersed dye to xylan was 0.1. A ball mill was used to grind the xylan / dye dispersed system, and the specific parameter conditions were: the mass ratio of the xylan dispersed dye system to the zirconium oxide beads was 1:5, the volume ratio of the zirconium oxide beads with diameters of 0.1 mm and 1.5 mm was 3:7, the grinding time was 4h, and the grinding speed was 400r / min.

[0044] Comparative Example 4

[0045] The eucalyptus wood is crushed to 40-60 mesh and then dried. 100g of absolutely dry raw material (water content is less than 15%) is weighed and mixed with a sodium hydroxide solution with a concentration of 5.00wt% at a solid-liquid ratio of 1:4 (w:v, unit is g / mL) in a rotary high-temperature reactor, and heated from room temperature (25℃) to 155℃ at a heating rate of 2℃ / min and then kept warm for 120min to complete the high-temperature reaction. After the reaction is completed, the reaction liquid is filtered and collected, and the pH is adjusted to 6.0 with hydrochloric acid, and then stirred and added to anhydrous ethanol (the volume ratio of the mixed liquid to ethanol is 1:3) to precipitate xylan, and after standing for 6h, the xylan is separated from the solid and liquid by centrifugation; the separated xylan is continuously washed with an ethanol solution with a volume percentage concentration of 70% for more than three times, and placed in a ventilated place to volatilize the ethanol, and then dried to obtain xylan.

[0046] Xylan and dispersed dark blue S-3BG 2007 dye were dispersed in water to form a xylan dispersed dye system, wherein the water was 70wt% and the mass ratio of dispersed dye to xylan was 5. The xylan / dye dispersed system was prepared by grinding in a ball mill, and the specific parameter conditions were: the mass ratio of the xylan dispersed dye system to the zirconia beads was 1:5, the volume ratio of the zirconia beads with diameters of 0.1 mm and 1.5 mm was 3:7, the grinding time was 4h, and the grinding speed was 400r / min.

[0047] Comparative Example 5

[0048] The commercial leveling agent sodium dodecylbenzene sulfonate and dispersed dark blue S-3BG 2007 dye were dispersed in water and ground using a ball mill to form a sodium dodecylbenzene sulfonate / dye dispersion system, which was used for the xylan / dye dispersion system of Comparative Example 2.

[0049] In the sodium dodecylbenzene sulfonate / dye dispersion system constituted by Comparative Example 5, water is 70wt%, and the mass ratio of disperse dye: sodium dodecylbenzene sulfonate is 2.75; the specific ball milling parameter conditions are as follows: the mass ratio of the dye system of sodium dodecylbenzene sulfonate leveling and zirconium oxide beads is 1:5, the volume ratio of zirconium oxide beads with diameters of 0.1mm and 1.5mm is 3:7, the grinding time is 4h, and the grinding speed is 400r / min.

[0050] Comparative Example 6

[0051] Potassium dihydrogen phosphate-dipotassium hydrogen phosphate buffer and dispersed dark blue S-3BG 2007 dye were dispersed in water and ground using a ball mill to form a potassium dihydrogen phosphate-dipotassium hydrogen phosphate / dye dispersion system for use in the xylan / dye dispersion system of Comparative Example 2.

[0052] In the potassium dihydrogen phosphate-dipotassium hydrogen phosphate / dye dispersion system constituted by Comparative Example 6, water is 70wt%, and the mass ratio of disperse dye: potassium dihydrogen phosphate-dipotassium hydrogen phosphate buffer is 2.75; the specific ball milling parameter conditions are as follows: the mass ratio of the potassium dihydrogen phosphate-dipotassium hydrogen phosphate buffered dye system to zirconium oxide beads is 1:5, the volume ratio of zirconium oxide beads with diameters of 0.1mm and 1.5mm is 3:7, the grinding time is 4h, and the grinding speed is 400r / min.

[0053] Table 1 shows the diffusion performance, dispersion stability of dyes, and reduction hydrolysis rate test results of the xylan / dye dispersion systems prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 6. It can be seen from the table that the dye dispersion systems prepared using xylan in Examples 1 to 4 have excellent diffusion effects and all meet the national standard for five-level diffusion; the reduction hydrolysis rates of the dye dispersion systems prepared in Examples 1 to 4 are significantly lower than 56.05% of Comparative Example 1, indicating that xylan has weaker destructive effect on dye reduction.

[0054] At present, the convenient and efficient method for improving the high temperature stability of the dye dispersion system usually relies on adding a dispersant or a leveling agent or a buffer. In the dye system using xylan as the dye dispersant, the average particle size after high temperature can reach as low as 216nm, which is much smaller than the particle size of the dye dispersed by adding commercial dye dispersant NNO (262nm), NMF (260nm), commercial leveling agent sodium dodecylbenzene sulfonate (241nm), and dye buffer potassium dihydrogen phosphate-dipotassium hydrogen phosphate buffer (270nm) in Comparative Examples 1, 2, 5, and 6, which proves the effectiveness of the high temperature stable dye dispersion system prepared in Examples 1 to 4.

[0055] (2) In Comparative Example 3, the amount of water used is within the middle range of the present invention, the weight ratio of disperse dye: xylan is lower than the lower limit of the preferred range of the present invention, and the dye diffusion is uneven (diffusion level is level 3), the reduction hydrolysis rate is high (59.09%), and the particle size of the dye dispersion system after high temperature treatment is higher than that of Examples 1 to 4.

[0056] (3) In Comparative Example 4, the amount of water used is within the middle range of the present invention, and the weight ratio of disperse dye:xylan is higher than the upper limit of the preferred range of the present invention. Compared with Examples 1 to 4, the dye reduction hydrolysis rate is high and the particle size of the dye dispersion system after high temperature treatment is higher than that of Examples 1 to 4.

[0057] Table 1 Test results of diffusion performance, dispersion stability and reduction hydrolysis rate of dye dispersion systems prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 6

[0058]

[0059] * Diffusion performance level: The test refers to HG / T3399-2001 "Dye Diffusion Performance Determination Method". Level 1 means very poor diffusion performance, level 2 means poor diffusion performance, level 3 means average diffusion performance, level 4 means good diffusion performance, and level 5 means very good diffusion performance.

[0060] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A dye dispersion system with high temperature stability, characterized in that: The invention is composed of disperse dye, xylan and water, wherein the weight ratio of the disperse dye to the xylan is 0.25-4, and the mass of the water is 60-90% of the dye dispersion system.

2. A dye dispersion system with high temperature stability according to claim 1, characterized in that: The disperse dye includes at least one of an azo disperse dye, an anthraquinone disperse dye, and a styrene disperse dye.

3. A dye dispersion system with high temperature stability according to claim 1, characterized in that: The xylan is obtained by extracting plant biomass raw materials.

4. A dye dispersion system with high temperature stability according to claim 3, characterized in that: The plant biomass raw material includes at least one of wood, bamboo, crop straw, the xylem of annual herbaceous plants, and fruit shells.

5. A dye dispersion system with high temperature stability according to claim 3, characterized in that: The extraction method comprises: an alkali solution extraction method, a dimethyl sulfoxide extraction method, and a low eutectic solvent extraction method.

6. A dye dispersion system with high temperature stability according to claim 1, characterized in that: The weight average molecular weight of the xylan is 20,000 to 100,000.

7. The method for preparing a dye dispersion system having high temperature stability according to any one of claims 1 to 6, characterized in that: The specific steps include: The xylan, water and disperse dye are mixed in a certain mass ratio to obtain a xylan / dye dispersion system, and then the xylan / dye dispersion system is mechanically ground to prepare the dye dispersion system with high temperature stability.

8. The preparation method according to claim 7, characterized in that: The mechanical grinding includes one of ball milling, sand milling and high pressure homogenization.

9. The preparation method according to claim 8, characterized in that: The parameters of the ball milling and sand milling methods are as follows: the type of grinding beads is selected from one of zirconium oxide beads, steel beads, and glass beads; the volume ratio of grinding beads with a diameter of 0.1 to 0.5 mm to grinding beads with a diameter of 1.5 to 3 mm is 7:3; the mass ratio of the xylan / dye dispersion system to the grinding beads is 1:5 to 1:30; the grinding time is 2 to 8 hours; and the grinding speed is 100 to 1000 r / min; In the high-pressure homogenization method, the high-pressure homogenization parameter conditions are as follows: homogenization pressure of 50 to 300 MPa, and the number of homogenization cycles of 5 to 10 times.